The impact of fiscal spending and financing by Sharia banks on economic growth in Indonesia - Risdiana Himmati; Badara Shofi Dana; Kesy Indraswari; Agus Salim (Indonesian Journal of Islamic Economics Research, 2024)
Economic activity can be increased by fiscal policy stimulus and financing by Sharia banks. This study aims to analyze the roles of fiscal policy and banking sector in driving Indonesia’s economic growth. Fiscal Policy, Macroeconomics, Financing, and Economic Growth are the variables used in this study. The data used is secondary data for the 2014-2023 period. This study uses the Error Correction Model (ECM) method. The results show that Fiscal Policy with proxy tax and government expenditure influence Economic Growth. On the other hand, the Financing of the banking sector influences Economic Growth.